2015
DOI: 10.1016/j.nifoj.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical properties of wheat-yam flour composite bread

Abstract: This work investigated the effect of yam flour substitution on characteristics of wheat bread and also determined the functional properties of the experimental flour samples. Flours were obtained from three varieties of yam (Dioscorea rotundata, Dioscorea alata and Dioscorea bulbifera) and blended with wheat flour at 25, 50 and 75 percent levels of substitution for bread production. Wheat flour (WF) and each of the yam flours were used as the positive and negative controls respectively. The functional properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
46
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 9 publications
12
46
1
4
Order By: Relevance
“…The deleterious effects of addition of fiber on dough structure and loaf volume are due to the dilution of gluten which in affects gas retention (Shittu et al, 2007). The low specific volume of the 100% fan root bread may be attributed to its lack of gluten that is responsible for enhanced dough rise in leavened wheat flour bread (Amandikwa et al, 2015).…”
Section: Physical Properties Of Breadsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deleterious effects of addition of fiber on dough structure and loaf volume are due to the dilution of gluten which in affects gas retention (Shittu et al, 2007). The low specific volume of the 100% fan root bread may be attributed to its lack of gluten that is responsible for enhanced dough rise in leavened wheat flour bread (Amandikwa et al, 2015).…”
Section: Physical Properties Of Breadsmentioning
confidence: 99%
“…The score for texture (softness and chewiness) decreased with the level of root flour. The baking conditions (temperature and time), state of the bread components such as fibers, protein (gluten), starch (whether damaged or undamaged) and the amount of water absorbed during dough mixing, contribute to final texture of bread (Amandikwa et al, 2015). It has been used to enhance the strength of gluten, handling and baking properties of dough and gas retention by oxidation of -SH groups of gluten protein to -SS groups.…”
Section: Sensory Properties Of Breadsmentioning
confidence: 99%
“…Out of several methods under consideration, the production of tortillas from composite flour is a viable approach [1] [5], which is achieved by substitution of wheat flour with other flour to make healthier tortillas. Previous studies have shown that yam flours have higher mineral content, higher dietary fiber content, higher resistant starch content, and lower estimated glycemic index (eGI) than refined wheat flour [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have been conducted on the use of wheat-yam composite flour for the production of bread, cake, and cookies [7] [17] [18]. However, there have not been any studies on the use of wheat-yam composite flours for the production of tortillas.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in water and oil absorption activity may be due to different protein concentration in wheat, sweet potato and tiger nut flours, their degree of interaction with water and oil and possibly the conformational characteristics. Water absorption capacity is important in dough consistency and baking quality of products (Amandikwa et al, 2015).…”
Section: Methodsmentioning
confidence: 99%